Ndae1 expression and regulation in Drosophila embryos. - Maria Florencia Tevy; Denis Seyres; Concetta Traina; Laurent Perrin; Maria Capovilla (PLoS ONE)
The construction and prediction of cell fate maps at the whole embryo level require the establishment of an accurate atlas of gene expression patterns throughout development and the identification of the corresponding cis-regulatory sequences. However, while the expression and regulation of genes encoding upstream developmental regulators such as transcription factors or signaling pathway components have been analyzed in detail, up to date the number of cis-regulatory sequences identified for downstream effector genes, like ion channels, pumps and exchangers, is very low. The control and regulation of ion homeostasis in each cell, including at blastoderm stages, are essential for normal embryonic development. In this study, we analyzed in detail the embryonic expression pattern and cis-regulatory modules of the Drosophila Na+-driven anion exchanger 1 (Ndae1) gene, involved in the regulation of pH homeostasis. We show that Ndae1 is expressed in a tight and complex spatial-temporal pattern. In particular, we report that this downstream effector gene is under the control of the canonical dorsal-ventral patterning cascade through dorsal, Toll, twist and snail at early embryogenesis. Moreover, we identify several cis-regulatory modules, some of which control discrete and non-overlapping aspects of endogenous gene expression throughout development.